Livestock and poultry excrement recycling method - HE LIN (2018)
The invention discloses a livestock and poultry excrement recycling method. The livestock and poultry excrement recycling method comprises the following steps of (1) respectively selecting cattle excrement, pig excrement, chicken excrement, calcium phosphate, magnesium phosphate, potassium chloride, rice straw powder, a compound microbial fermenting agent and water, and uniformly mixing, so as toobtain a mixture; (2) composting the mixture in step (1), covering one layer of pond sludge with thickness of 2 to 5cm at the surface of the material pile, and fermenting for 10 to 20 days. The livestock and poultry excrement recycling method has the advantages that the respective physical properties and nutrients of the cattle excrement, pig excrement and chicken excrement are utilized, and the external fertilizer compounds are added to compound, so as to regulate the balance of the fertilizer; the fertility balance efficiency of the prepared organic fertilizer is high. 本发明公开了种畜禽粪便资源化处理方法，包括：（1）分别取牛粪、猪粪、鸡粪、磷酸钙、硫酸镁、氯化